2016
DOI: 10.1177/1558944715627627
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a Recurrent Neuroma Within Nerve Allograft With Autologous Nerve Reconstruction

Abstract: In the setting of recalcitrant neuromas and intractable pain following multiple neuroma excisions, allografts may be suboptimal in reconstruction of larger gap defects. Autologous reconstruction with porcine submucosa extracellular matrix, as in this case, can avoid tethering, local ischemia, and nerve traction to optimize outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Finger injury is the most common type of injury in children in emergency department, which has a certain impact on their body and mind [1,2]. Although most children have mild finger injuries, severe finger injuries still need surgical treatment [3,4] and may lead to serious complications such as infection, soft tissue defect, fracture nonunion, and ampu-tation, resulting in serious sequelae such as finger deformity, nail dysplasia, and intractable pain [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Finger injury is the most common type of injury in children in emergency department, which has a certain impact on their body and mind [1,2]. Although most children have mild finger injuries, severe finger injuries still need surgical treatment [3,4] and may lead to serious complications such as infection, soft tissue defect, fracture nonunion, and ampu-tation, resulting in serious sequelae such as finger deformity, nail dysplasia, and intractable pain [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…3 ). 14 , 15 , 16 , 17 , 18 While numerous techniques have been described to treat painful neuromas, the optimal surgical technique for management and treatment of neuroma patients remains elusive. 27
Figure 3 Neuroma pain that is amenable to surgery.
…”
Section: Neuroma Painmentioning
confidence: 99%
“…Painful neuromas represent perhaps the best understood neuralgic phenomena. 14 , 15 , 16 , 17 , 18 Studies led by Campbell et al 15 on neuroma pathophysiology showed ephaptic conduction within the neuroma that was mechanically sensitive but also spontaneously active; this pathophysiologic phenomenon resonates with the clinical narratives given by those with neuroma pain. An injury with Sunderland degree V—complete transection—is a typical neuroma, with degree IV representing a neuroma in continuity (with potential for a degree VI mixed injury in the nerve in this context).…”
mentioning
confidence: 93%
“…In digital nerves, frequently seen after amputation, simple shortening and burring nerve end can be satisfactory. In recurrent cases or other techniques are proposed including end-to-side suture of injured nerve to the healthy one, introducing the nerve end into the bone or use of allografts (Sosin et al, 2016).…”
Section: Other Proceduresmentioning
confidence: 99%